2014
DOI: 10.1016/j.bbr.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orbitofrontal cortex lesions on autoshaped lever pressing and reversal learning

Abstract: A cue associated with a rewarding event can trigger behavior towards the cue itself due to the cue acquiring incentive value through its pairing with the rewarding outcome (i.e., sign-tracking). For example, rats will approach, press, and attempt to “consume” a retractable lever conditioned stimulus (CS) that signals delivery of a food unconditioned stimulus (US). Attending to food-predictive CSs is important when seeking out food, and it is just as important to be able to modify one’s behavior when the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Previous studies indicate crucial involvement of the prefrontal cortex (PFC) in reversal learning. One PFC region, the orbitofrontal cortex (OFC), is thought to be particularly important, as OFC lesions consistently result in impaired reversal learning (47)(48)(49)(50)(51)(52)(53)(54). SAPAP3 -/display altered OFC-striatal activity (16,17) and deficits in behavioral response inhibition that can be rescued by optogenetic stimulation of the OFC-striatal network (19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate crucial involvement of the prefrontal cortex (PFC) in reversal learning. One PFC region, the orbitofrontal cortex (OFC), is thought to be particularly important, as OFC lesions consistently result in impaired reversal learning (47)(48)(49)(50)(51)(52)(53)(54). SAPAP3 -/display altered OFC-striatal activity (16,17) and deficits in behavioral response inhibition that can be rescued by optogenetic stimulation of the OFC-striatal network (19).…”
Section: Discussionmentioning
confidence: 99%
“…As with the cohort approach, all animals tested herein were exposed to PCA training with a lever, leading to the question of why there was so little goal-tracking observed to the lever in the present experiments. Others (Boakes 1977;Davey et al 1982;Chang et al 2012;Chang and Holland 2013;Chang 2014;Holland et al 2014) have observed a similar bias toward sign-tracking to a lever as that observed herein when training took place in conjunction with an additional control lever that was never followed by food (Lever2); consistent with this hypothesis, both sign-tracking rates to the lever and goal-tracking rates to the tone were higher in the 4-CS PCA experiment, where both stimuli were trained with a never-reinforced counterpart (Lever2 and Tone2). Additionally, Other than the single between-subject experiment presented herein (although no goal-trackers were identified in that experiment either), all animals were trained with at least one additional stimulus, leaving open the possibility that including any element of discrimination in training may promote sign-tracking to the food-associated lever (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, lights are known to elicit goal-tracking behavior (Holland, 1977; Cleland and Davey, 1983; Beckmann and Chow, 2015), described as approach to the location of reward delivery (Boakes, 1977), when a food US is used and are not accompanied by the attribution of incentive value that has been shown to promote suboptimal choice behavior. Importantly, it has been shown that rats have a tendency to sign-track to a lever CS (Davey et al 1982; Chang, 2014; Holland et al 2014), and levers associated with sign-tracking behavior function as robust conditioned reinforcers (Robinson and Flagel, 2009). Therefore, in the present study we examined how different terminal-link stimuli, with and without incentive salience (i.e., levers vs. lights), can influence decision-making in rats using a suboptimal choice procedure (Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%